The Effect Of NaOH Concentration And Microwave Heating Time On Pretreatment Process Toward Lignocellulose Content Of Chlorella vulgaris - Siregar, Moh. Risal; Hendrawan, Yusuf; Nugroho, Wahyunanto Agung (Jurnal Teknologi Pertanian, 2014)
The scarcity of fossil fuel, cause necessary a renewable energy such as bioenergy with biomass as resources. One of biomass resources which can be used is microalgae Chlorella vulgaris. The aim of this research is to learn the effect of NaOH concentration and microwave heating time toward content of cellulose, lignin and hemicellulose Chlorella vulgaris. 15 grams powder of Chlorella vulgaris is mixing with 150 ml NaOH (0.3M ; 0.5 M ; 0.7 M) and then be heated on microwave PANASONIC model NN-GD371M (f = 2450 MHz ; P = 950 Watt) at low temperature level with time variations that 20 meniutes, 30 minutes, 40 minutes. The result of effectivity indeks analyze, the best treatment on 0,7 M 40 menit. Cellulose content go down from 1.27% to 0.53%, hemicellulose go up from 17.02% to 0.65% and lignin go up from 0.27% to 0.65% or can be said carbohydrat go up from 18.29% to 67.49%. Microstructure analysis with SEM show that structure of molecules changed, destroyed and not compact. Key Words : Chlorella vulgaris, Microwave-NaOH, Pretreatment